Predictors of binge drinking among adults in Autonomous Province of Vojvodina, Serbia: Data from the population-based behavioral risk-factors surveillance system - Tanja Tomašević; Ivana Radic; Vesna Mijatović Jovanović; Snežana Ukropina; Dragana Milijašević; Sonja Čanković; Radmila Petrović; Vladimir Petrovic (PLoS ONE, 2026)
Introduction Alcohol use has been linked to harmful health outcomes. In this study, we examined the association between binge drinking and sociodemographic characteristics as well as health-related lifestyle factors among the adult population in Autonomous Province of Vojvodina (APV). Materials and methods The data for this study were used from the newly established “Surveillance of Behavioural Risk Factors for Non-Communicable Diseases in Vojvodina” (SBRF-NCD-V) system in APV, Serbia. This cross-sectional study involved 3910 healthcare users aged 18 years and older, interviewed in 2024, across all 44 Primary Healthcare Centers in APV. The questionnaire used was adapted from the BRFSS instrument developed by the CDC. A multivariable binary logistic regression model analysed associations between binge drinking and sociodemographic, as well as health-related factors, stratified by gender to calculate odds ratios. Results The prevalence of binge drinking in Vojvodina was high (19.3%). Higher odds of binge drinkers were recorded in males (OR=4.3; 95% CI = 3.5–5.2; p < 0.001), in younger categories compared to age groups 65 and over (p < 0.001), never married females compared to married/living with a partner (OR=2.1; 95% CI = 1.4–3.5; p = 0.002), females with poor/very poor material status (OR=2.1; 95% CI = 1.2–3.9; p = 0.014), females who were former smokers (OR=1.8; 95% CI = 1.1–3.3; p = 0.033) or smokers (OR=2.8; 95% CI = 2.3–3.5; p < 0.001) compared to non-smokers, males who were not physically inactive (OR=1.7; 95% CI = 1.3–2.2; p < 0.001). Conclusion Factors contributing to the high prevalence of binge drinking in APV, Serbia, were gender, younger age, never-married status in females, worse material status in females, former smoking in females, smoking for both genders, and physical activity in males. Introducing a continuous sub-national surveillance system could significantly improve the monitoring of factors associated with alcohol use prevalence. Identified sociodemographic factors could help health workers in primary care settings to screen and support patients at risk of, or engaged in risky alcohol use.